Teacher Constraints at Madrasah Ibtidaiyah YKUI Maskumambang Gresik in The Perspective of Educational Supervision - Fakhlipi, Muhammad Rafeli; Aisyah, St (Universitas Negeri Malang, 2024)
Abstract: The quality of teachers can be viewed from the level of professionalism in order to realize all matters related to teaching and learning activities for students. Teachers generally have difficulty in determining the suitable learning method in the classroom, especially teachers who are already old so they still use the old method, namely one-way learning that makes the class feel less alive so that it is no longer relevant to the times and requires innovation. Another problem for teachers is that they experience many problems regarding learning devices ranging from lack of knowledge in their manufacture to laziness in making them even though learning devices are a very essential component in teaching and learning activities. Most teachers also have a low level of self-awareness in submitting themselves to be supervised so that their teaching in the classroom gets an evaluation. Departing from these assumptions, the author is encouraged to conduct research with a focus on problems related to teacher constraints in madrasah Ibtidaiah YKUI Maskumambang Gresik in the perspective of educational supervision. Keywords: MI YKUI Maskumambang; Teacher Constraints; Educational Supervision